Vegetation and snow effects on soil-atmosphere heat exchange: 2024/25 winter study - Frolov D. M.; Seliverstov Y. G.; Koshurnikov A. V.; Gagarin V. E.; Nikolaeva E. S.; Sidorova T. A. (BIO Web of Conferences)
The paper aimed to understand soil-atmosphere heat exchange influenced by vegetation and snow cover. An observational system was implemented to monitor ground, snow, and near-surface air temperatures beginning in the 2024/25 winter season. The onset of snow cover in Moscow was on November 23–25, 2024, occurring 10 days later than the 1991–2000 average. By December 8, significant snowfall increased snow depth to 14 cm, with variations across Moscow and its regions. Observations revealed a complex snow layer structure and temperature profiles throughout December. January 2025 was marked by intermittent thaws, leading to snow cover disappearance, with January temperatures approximately 6°C above normal. The snow cover re-onset took place only in the middle of February, which was the coldest month of this winter period. The study highlights the impact of vegetation and snow on soil temperature dynamics and surface soil frost events were recorded.